Efektivitas rondo dalam meningkatkan passing pemain futsal putri - Azhari, Muhamad Robbih; Abidin, Dindin (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam 45, 2022)
Passing is one of the basic futsal techniques that is very important to be mastered by futsal athletes because by passing a player can attack the opponent and produce points. Rondo is one of the terms of the cat-and-mouse game is a method to improve passing skills that is implemented at all levels of soccer players. Rondo is one of the games that can develop passing techniques well. The method used in this research is experimentation using test and measurement instruments. The population in this study were 25 people. The sample used in this study was 15 people using purposive sampling. The data analysis requirements used are normality and homogeneity tests. The data analysis used in this study used the t-test. From the results of data analysis, researchers have processed data using statistics and the results of data processing and data analysis obtained answers to the formulation of problems and objectives of the research above as follows: from the results of the t-test, the value of t count for rondo training (passing accuracy) obtained a value of 34.2. This value is greater than the t table at the real level (ɑ) = 0.05 and degrees of freedom (dk) = 26.1 so that the research hypothesis (H1) is accepted.